Using bluetooth as the connecting interface between Arduino and a brain-computer interface - Goh, Weysyee (2015)
Brain-controlled interface (BCI) is a new technology derived from electroencephalography (EEG), which allows human to send commands through BCI via electrical activity from their brain instead of moving their limbs. BCI used in this paper uses Bluetooth technology to send data information received from brain activities of human and allows computer to process the data to be transmitted to robotic limbs or Arduino robot used in this paper, and hence allowing movements to occur. Bluetooth technology offers short-range data transmission with very low power consumption. This project aims to write a program to connect BCI and Arduino robot via Bluetooth in which the expected outcome would be a stable wireless connection of BCI and Arduino via Bluetooth without any other Bluetooth or WI-Fi interference. It also aims to write a program to establish a bridge between sa and Arduino motor and make sure it functions without any distraction. For this, HC-05 Bluetooth Module will be used as the bridge between BCI and Arduino. Different tests were done to ensure stability of the Bluetooth connection such as interference test, obstacle test and load test. There was no interference from other electromagnetic signal sources i.e. Wi-R and Bluetooth due to frequency hopping feature. Obstacles such as walls, doors and iron pipes between walls cause diffraction and absorption, which weakens the Bluetooth signal. The connection is also tested with LED only and Arduino robot, which uses different power, but the load does not affect Bluetooth connection. As for the conclusion, a stable Bluetooth connection is established.